Scythians in Azerbaijan: the history of one murder (archaeology and anthropology) - Kirichenko Dmitry A. (Поволжская археология)
The article presents craniological materials of the Early Iron Age (VII–IV centuries BC) from Mingachevir. The study examined the skull of a female (2488) aged 20–30 years with evidence of traumatic injury. Caucasoid, mesocranial, originating from the burial with the skeleton in extended position (No. 137), which correlates with the presence of the Scythians on the territory of our republic. The depressed compression fracture, 0.9 cm in diameter, from which cracks radiate, was marked on the left part of upper section of the frontal bone of the woman’s skull. There are no signs of healing or inflammation. The crime weapon was a hard, blunt object, that broke and pressed the bone, after which a round-shaped dent was formed, and cracks appeared from it, which indicates the significant force of the blow, which led to the death of the woman. We can observe the so-called perimortem trauma - injury got at or near the moment of death. The blow was struck, presumably, from the right and from above; the victim was below the killer, who could be on horseback, and at a distance from the deceased. The case from Mingachevir is currently the only anthropological find of this kind - a fatal compression fracture of the cranial vault from the territory of Azerbaijan during the Early Iron Age.